Wearable technology-delivered lifestyle intervention amongst adults with overweight and obese: A systematic review and meta-regression. (March 2022) - Wong, Sai Ho; Tan, Zhen Yang Abel; Cheng, Ling Jie; Lau, Siew Tiang
Abstract: Background: Globally, overweight and obesity are becoming a growing concern, and wearable technology combined with lifestyle intervention may offer an innovative solution. Objective: This review aimed to (1) assess the effectiveness of lifestyle interventions delivered by wearable technology in improving weight loss and physical activity among overweight or obese adults and (2) explore the effects of covariates on intervention outcomes. Design: Systematic review, meta-analysis and meta-regression. Methods: The criteria for inclusion in the review were that the trial must be a lifestyle modification intervention that utilised wearable technology and had a randomised control design and obese or overweight participants aged 18–64 years. Ten electronic databases were searched from inception to 8 December 2020. The Cochrane Risk of Bias Tool version 1 and Grading of Recommendations, Assessment, Development and Evaluations were adopted to rate risk of bias of individual trials and certainty of evidence, respectively. Stata 16 software was used to conduct the meta-analysis, subgroup analysis and meta-regression analysis. Results: Thirty trials comprising 5, 391 adults from 11 countries were included. Meta-analyses found significant changes in weight (−1.08 kg, 95% confidence interval, CI: −1.88, −0.28), body mass index (−0.36 kg/m 2, 95% CI: −0.62, −0.09), waist circumference (−1.12 cm, 95% CI: −2.08, −0.16), steps per day (1, 243.51 steps, 95% CI: 111.51, 2375.51), steps per day change (456.18 steps, 95% CI: 40.61, 871.76), systolic pressure (−2.57 mmHg, 95% CI: −4.57, −0.56) and diastolic pressure (−2.10 mmHg, 95% CI: −3.43, −0.77). Significant differences were found between subgroups regarding region ( Q  = 7.35, p  = 0.01), lifestyle component ( Q  = 8.51, p  = 0.01) and registration protocol ( Q  = 20.24, p < 0.01). The multivariable meta-regression model suggested that year of publication (adjusted β  = 0.20, 95% CI: 0.07, 0.34, p  = 0.003), mean age (adjusted β  = −0.94, 95% CI: −0.14, 0.04, p < 0.001) and duration (adjusted β  = 0.17, 95% CI: 0.09, 0.25, p < 0.001) had significant effects on the mean difference of weight change. Discussion: The majority of the certainty of evidence was graded moderate to high, which suggests that interventions utilising wearable technology may improve body mass index, waist circumference and physical activity of participants. These findings may aid in the development of future health interventions. However, the current review was limited to self-selected samples and trials conducted in English. Registration: PROSPERO Number: CRD42021232871  (Blind ID)